LABOR MARKET OPENNESS, H‐1B VISA POLICY, AND THE SCALE OF INTERNATIONAL STUDENT ENROLLMENT IN THE UNITED STATES. (3rd September 2015) - Shih, Kevin
Abstract : International students have long comprised an important part of U.S. higher education. However, little is known regarding the factors that encourage students from across the world to enroll in U.S. colleges and universities each year. This paper examines the relationship between international enrollment and the openness of the United States' skilled labor market, currently regulated by the H‐1B program. Gravity regressions reveal that H‐1B visa issuances to a country are positively and significantly related to the number of international students from that country. Causal estimates of the impact of labor market openness are achieved by exploiting a dramatic fall in the H‐1B visa cap in October 2003. Triple difference estimates show that the fall in the cap lowered foreign enrollment by 10%. ( JEL F22, I21, J11)